Hepatic splenosis mimicking liver metastases in a patient with history of childhood immature teratoma - Jereb, Sara (Radiology and oncology (Ljubljana), 2016)
Hepatic splenosis is rare condition, preceded by splenectomy or spleen trauma, the term refers to nodular implantation of normal splenic tissue in the liver. In patients with history of malignancy in particular, it can be mistaken for metastases and can lead to unnecessary diagnostic procedures or inappropriate treatment. Case report. Twenty-two-year old male was treated for immature teratoma linked to undescended right testicle after birth. On regular follow-up examinations no signs of disease relapse or long-term consequences were observed. He was presented with incidental finding of mature cystic teratoma after elective surgery for what appeared to be left-sided inguinal hernia. The tumour was most likely a metastasis of childhood teratoma. Origin within remaining left testicle was not found. Upon further imaging diagnostics, several intrahepatic lesions were revealed. Based on radiologic appearance they were suspicious to be metastases. The patient underwent two ultrasound guided fine-needle aspiration biopsies. Cytologic diagnosis was inconclusive. Histology of laparoscopically obtained tissue disclosed presence of normal splenic tissue and led to diagnosis of hepatic splenosis. Conclusions. Though hepatic splenosis is rare, it needs to be included in differential diagnosis of nodular hepatic lesions. Accurate interpretation of those lesions is crucial for appropriate management of the patient. If diagnosis eludes after cytologic diagnostics alone, laparoscopic excision of nodular lesion is warranted before considering more extensive liver resection.
Keywords: hepatic splenosis; jetrna splenoza; laparoscopy; laparoskopija; metastases; teratom; teratoma; zasevki